Where tulips and crocuses are popular food snacks: Kurdish traditional foraging reveals traces of mobile pastoralism in Southern Iraqi Kurdistan - Andrea Pieroni; Hawre Zahir; Hawraz Ibrahim M. Amin; Renata Sõukand (BMC, 2019)
Abstract Background Iraqi Kurdistan is a special hotspot for bio-cultural diversity and for investigating patterns of traditional wild food plant foraging, considering that this area was the home of the first Neolithic communities and has been, over millennia, a crossroad of different civilizations and cultures. The aim of this ethnobotanical field study was to cross-culturally compare the wild food plants traditionally gathered by Kurdish Muslims and those gathered by the ancient Kurdish Kakai (Yarsan) religious group and to possibly better understand the human ecology behind these practices. Methods Twelve villages were visited and 123 study participants (55 Kakai and 68 Muslim Kurds) were interviewed on the specific topic of the wild food plants they currently gather and consume. Results The culinary use of 54 folk wild plant taxa (corresponding to 65 botanical taxa) and two folk wild mushroom taxa were documented. While Kakais and Muslims do share a majority of the quoted food plants and also their uses, among the plant ingredients exclusively and commonly quoted by Muslims non-weedy plants are slightly preponderant. Moreover, more than half of the overall recorded wild food plants are used raw as snacks, i.e. plant parts are consumed on the spot after their gathering and only sometimes do they enter into the domestic arena. Among them, it is worth mentioning the consumption of raw wild crocus corms, also still common in Turkish Kurdistan and that of wild tulip bulbs, which was documented to be popular until the beginning of the twentieth century in the Middle East. Comparison with other ethnobotanical field studies recently conducted among surrounding populations has shown that Kurds tend to gather and consume the largest number of non-weedy wild vegetables. Conclusion The collected data indicate robust traces of nomadic pastoralism in Kurdish traditional foraging. This finding confirms that studies on wild food plant gathering in the Fertile Crescent and Turco-Arabic-Iranic regions of the Middle East are crucial for understanding the possible evolution of wild food plant gathering through history within the post-Neolithic continuum between pastoralism and horticulturalism.